THE ENLIGHTENING MESSAGE OF EVANGELICAL MOVEMENT: A GENETIC STRUCTURALISM STUDY ON A CHRISTMAS CAROL BY CHARLES DICKENS - Hafidhun Annas (PARADIGM: Journal of Language and Literary Studies, 2021)
A Christmas Carol is a novel by Charles Dickens full of social criticism and is framed in the story of the Christmas majesty. This study aims to reveal the structure of a novel A Christmas Carol in relation to the Evangelical movement in England during the Victorian era. This study employs the theory of Genetic Structuralism by Lucien Goldmann. The result of the analysis shows that the Christmas ghosts can change the characters, setting, and plot of the novel because the they deliver the main idea of the novel, which is the enlightenment message of Evangelical movement. The message is about human kindness, mutual assistance, and death.